RESISTANCE OF IRAQI WHEAT CULTIVARS TO COMMON BUNT DISEASE AND MOLECULAR DIAGNOSIS OF THE AVIALABLE BT GENES IN EACH CULTIVAR - Emad M. Al-Maaroof; P. H. Saed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to identify resistance sources in the Iraqi wheat cultivars using pathological and molecular approaches. Results revealed that forty-four reeleased wheat cultivars were divided into four groups according to their mean infection percentage to common bunt disease. Resistant group consists of wheat cultivars Farris 1, Ashur, Tamuz 3, AlMadian, AlBaraka, Latiffiya, and Rabia. The mean infection percentage of this group ranged from 0.28-3.98% and significantly was higher than that of all other groups during two growing seasons. Moderately resistant cultivars included cv’s Bura, Iratom, Charmo, Maaroof, and AlRasheed with mean infection range of 10.39- 21.10%. The majority of the tested cultivars (63%) explored high susceptibility to the disease (52.14-91.97%) while the mean infection of the susceptible group ranged from 31.51% in Buhoth 22 to 47.47% in Wafia. Molecular analysis using SSR markers GWM7433, XGWM114, and XGWM264 revealed that Charmo and Hsad- possess the resistance gene Bt9 at 296bp, while Buhoth 10 possesses the known resistance gene Bt12 at 175bp. All the tested cultivars not contain the known resistance genes Bt8, Bt10, and Bt11. The high resistance level of the resistant group could be attributed to the presence of additional known resistance Bt genes or other unidentified resistance genes.